Impact of Advertisements on Philippine Financial Service Firms’ Stock Returns - Centeno, Dave DG.; Yusoph, Al-Habbyel B. (Philippine Management Review; Vol 28 (2021), 2023)
A growing interest in marketing literature has been on establishing the impact of advertising on stock value. This study illustrates the impact of advertising and celebrity endorsements on daily stock returns among publicly listed banks and other financial service firms in the Philippines. Print advertisements published in 2016 in two major broadsheets are archived and coded on the presence or absence of advertisements and celebrity endorsements. Findings show that the presence of advertisements has a marginally significant positive effect on daily stock returns one trading day after the appearance of the advertisement, while the presence of celebrity endorsements has none. The signaling-and-spillover function of advertising is used to theoretically explain the associated effect on stock price – investors perceive the company’s prospective performance based on the heuristics of advertisements.